2008
DOI: 10.1177/0886260508314330
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Violence in the Family of Origin and Dating Violence Among College Students

Abstract: Prior research has established that violence in dating relationships is a serious social problem among adolescents and young adults. Exposure to violence during childhood has been linked to dating violence victimization and perpetration. Also known as the intergenerational transmission of violence, the link between violence during childhood and dating violence has traditionally focused on physical violence. This research examines the relationship between experiencing and perpetrating dating violence and exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
236
2
21

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(290 citation statements)
references
References 53 publications
31
236
2
21
Order By: Relevance
“…Their findings indicated that the likelihood for perpetrating physical intimate partner violence was strongest when male and female emerging adults reported a history of exposure to interparental violence perpetrated by the same sex parent. Despite these findings and previous evidence supporting a gender identification model of the IGT of violence, this model has not been consistently supported (e.g., Gover et al, 2008). As such, these findings are far from conclusive and further research on the IGT of violence that considers the role of gender is needed to better understand its impact on the transmission process.…”
Section: Gendermentioning
confidence: 40%
See 1 more Smart Citation
“…Their findings indicated that the likelihood for perpetrating physical intimate partner violence was strongest when male and female emerging adults reported a history of exposure to interparental violence perpetrated by the same sex parent. Despite these findings and previous evidence supporting a gender identification model of the IGT of violence, this model has not been consistently supported (e.g., Gover et al, 2008). As such, these findings are far from conclusive and further research on the IGT of violence that considers the role of gender is needed to better understand its impact on the transmission process.…”
Section: Gendermentioning
confidence: 40%
“…Further, there is evidence that experiences of physical maltreatment and neglect in childhood are related to reported injuries sustained through intimate partner violence (Ehrensaft et al, 2003). However, it should be noted that most research on the IGT of violence has utilized cross-sectional study designs and variable-oriented methods and has provided inconsistent support for relationships among varying forms of experienced maltreatment and intimate partner violence (e.g., Gover, Kaukinen, & Fox, 2008;Rivera & Fincham, 2015;Simons, Simons, Lei, Hancock, & Fincham, 2012).…”
Section: Intergenerational Transmission Of Violencementioning
confidence: 99%
“…Previous findings also suggest that gender, education, physical aggression, hostility, childhood abuse and exposure to domestic violence, and history of partner violence are risk factors for relationship violence (Burt, 1980;Cowan, 2000;Chen and White, 2004;Gover et al, 2008;White and Smith, 2009;Gallagher, 2011). Preliminary findings in this study suggest that these variables are equally vital to understanding BEREVIWOS and GESTABE.…”
Section: Discussionmentioning
confidence: 62%
“…For example, psycho-emotional, situational, and psychopathological factors have been identified as risk factors for partner violence (Gordon, 2000;Straus, 2009;Hyde-Nolan and Juliao, 2011). In the same vein, physical aggression, hostility (i.e., readiness for physical aggression), childhood history of abuse, exposure to domestic violence, and history of perpetrating partner violence have been associated with relationship violence (Cowan, 2000;Gover et al, 2008;White and Smith, 2009;Gallagher, 2011). Also, adversarial sexual beliefs and approval of patriarchal norms have been associated with endorsement of sexual violence and lower propensity to validate spousal abuse (Burt, 1980;Ahmad et al, 2004).…”
Section: Gender-based Relationship Violence and Socio-demographic Facmentioning
confidence: 99%
See 1 more Smart Citation